Characterisation of oxygen permeation into a microfluidic device for cell culture by in situ NMR spectroscopy. Issue 11 (6th May 2016) - Yilmaz, Ali; Utz, Marcel
Abstract : A compact microfluidic device for normoxic perfusion culture of mammalian cells under in situ metabolomic observation by NMR spectroscopy is presented. Abstract : A compact microfluidic device for perfusion culture of mammalian cells under in situ metabolomic observation by NMR spectroscopy is presented. The chip is made from poly(methyl methacrylate) (PMMA), and uses a poly(dimethyl siloxane) (PDMS) membrane to allow gas exchange. It is integrated with a generic micro-NMR detector developed recently by our group [ J. Magn. Reson., 2016, 262, 73–80]. While PMMA is an excellent material in the context of NMR, PDMS is known to produce strong background signals. To mitigate this, the device keeps the PDMS away from the detection area. The oxygen permeation into the device is quantified using a flow chemistry approach. A solution of glucose is mixed on the chip with a solution of glucose oxidase, before flowing through the gas exchanger. The resulting concentration of gluconate is measured by 1 H NMR spectroscopy as a function of flow rate. An oxygen equilibration rate constant of 2.4 s −1 is found for the device, which is easily sufficient to maintain normoxic conditions in a cell culture at low perfusion flow rates.